Socio-environmental factors and prevalence of enteroparasites in hemodialysis patients in the Pantanal of Mato Grosso state, Brazil (Research, Society and Development, 2020)
Hemodialysis patients due to their reduced immune system are easily affected by enteroparasites, which lead to a worsening of the health status of these individuals. The aim of this research was to identify the prevalence of enteroparasites in chronic renal patients undergoing hemodialysis and possible associations with socioenvironmental factors. This is a cross-sectional study with 53 patients. Pearson's chi-square (x²) and Odds Ratio (OR) tests were used for association analysis. Coprological examinations were analyzed using the techniques of Hoffman and Sheather. The positivity of enteroparasites reached 92.5%, with Blastocystis sp. the most prevalent (95.9%). Regarding helminths, only Ascaris lumbricoides was found (4.1%). Mixed infections appeared in 53% of cases. The most common double association was between Blastocystis sp. and Endolimax nana, observed in 22.4% of cases. Our results showed a high prevalence of protozoa with worrying repercussions for the health of these patients, such as Cryptosporidium sp., Giardia lamblia and Entamoeba histolytica, showing the need for strategies to prevent parasitic infections and appropriate interventions in hemodialysis patients.